The Potential Use of Invasive Ascidians for Biomonitoring Heavy Metal Pollution - Tzafriri-Milo, Roni; Benaltabet, Tal; Torfstein, Adi; Shenkar, Noa (Frontiers in Marine Science, 2019)
Heavy metal inputs into marine environments and their effect on marine organisms are of major concern. Here, we examined the potential use of two invasive ascidian species, Phallusia nigra and Microcosmus exasperatus, as bio-indicators of 11 HMs in the Mediterranean and Red Sea coasts of Israel. Individuals were collected on a seasonal basis from three sites over one year, and analysis was carried out seperatly for the tunic and the body. Both species accumulated high levels of HMs, which varied seasonally and spatially. In M. exasperatus the majority of HMs were found in the tunic, and in P. nigra in the body, suggesting the need to analyze total individuals in future studies. Hepato-Somatic Index values for M. exasperatus were significantly lower at the polluted site. Investigation of a popular public beach revealed high levels of certain dissolved HMs in both the water and in the ascidians. The wide geographic distribution and high filtration capacity of invasive ascidians offer great potential for their use in monitoring metal pollution in marine environments.